Precuneal hyperperfusion in patients with attention-deficit/hyperactivity disorder-comorbid nociplastic pain - Takahashi, Miwako; Kasahara, Satoshi; Soma, Tsutomu; Morita, Taito; Sato, Naoko; Matsudaira, Ko; Niwa, Shin-Ichi; Momose, Toshimitsu (Frontiers in Pharmacology, 2024)
Introduction Nociplastic pain (NP), a third category of chronic pain, offers a framework for elucidating its pathophysiology and treatment strategies. One of the characteristics of NP is comorbidity of symptoms other than pain, such as psychological and cognitive problems; therefore, these can be clues to understanding NP. Recently, we reported several cases with comorbid symptoms of attention-deficit/hyperactivity disorder (ADHD). Notably, ADHD medications, including methylphenidate (MP) and atomoxetine, improved chronic pain as well as the symptoms of ADHD. However, in clinical settings, identifying comorbid ADHD in patients with chronic pain is challenging, and underlying mechanisms have not been elucidated. To explore the common characteristics of brain function in patients with ADHD-comorbid NP, we identified brain regions where cerebral blood flow (CBF) distributions changed between pre- and post-treatment using single-photon emission computed tomography (SPECT). Additionally, we examined brain regions where CBF values correlated with clinical scores. Methods We retrospectively studied 65 patients (mean age 53 ± 14 years; 30 males and 35 females) with ADHD-comorbid NP who underwent CBF-SPECT before and after ADHD medication initiation. Clinical scores included the clinical global impression severity (CGI-S), pain numerical rating scale, hospital anxiety and depression scale, pain catastrophizing scale, and Conners’ adult ADHD rating scale-self report scores. Voxel-based statistical methods were used to compare pre- and post-treatment CBF-SPECT images to identify significant differences and investigate brain regions correlated with clinical scores. Results The CBF was higher in the precuneus, insular gyrus, and thalamus before treatment than after treatment (paired t-test, cluster-definition p < 0.001, cluster-extent threshold p < 0.05, with family-wise error [FWE] correction). The hyperperfusion in the precuneus was positively correlated with the CGI-S score and significantly reduced after treatment with MP (paired t-test, cluster-definition p < 0.005, cluster-extent threshold p < 0.05, with FWE correction). Conclusion The finding of precuneal hyperperfusion may provide insight into the mechanisms of NP and help identify patients who would benefit most from ADHD medications.